Views on the low productivity of GOCCs - Milla, Sarah Amabelle A. (Philippine Journal of Labor and Industrial Relations, 2003)
Given the evident frailty and instability of the Philippine economy, the necessity for the government to manage its available resources with utmost prudence cannot be understand. One of the areas being scrutinized is the government corporate sector consisting of Government-Owned and/or Controlled corporations (GOCCs). Some GOCCs have remained dependent on the national government for funding support. But with the downward trend that our economy has been experiencing and the ballooning budget deficit that our country is facing, the need to enhance the productivity of these GOCCs should be taken seriously. The overall poor performance of GOCCs, in terms of profitability and efficiency could be attributed to certain factors, foremost if which are: (a) the fact that they are expected to pursue both commercial and social goals, (b) the inability of the government to finance capital intensive corporations such as those belonging to the power sector (c) the "bureaucratization" of management- weak delegation of administrative responsibility and decision-making is highly top to bottom in orientation and (d) minimal participation from the employees in terms of program and project formulation. The paper presents the view that there alternatives other than privatization of the poorly reforming GOCCs for these to raise their productivity.